2016
DOI: 10.1177/0218492316686477
|View full text |Cite
|
Sign up to set email alerts
|

Saccular aneurysm of external jugular vein with partial thrombosis

Abstract: Venous aneurysms are uncommon clinical entities. Venous aneurysms involving the head and neck region are distinctly uncommon, and a saccular aneurysm of the external jugular vein with thrombus is extremely rare. We present a case of saccular aneurysm of the external jugular vein with partial thrombosis in a 30-year-old woman, which was diagnosed on duplex ultrasound and contrast-enhanced computed tomography, and treated by surgical excision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 5 publications
0
10
0
6
Order By: Relevance
“…Several authors confirmed that anticoagulation alone is insufficient for preventing such complications [ [25] , [26] , [27] , [28] ]. Most patients with external jugular vein aneurysm underwent surgical treatment with local, and general anesthesia [ 16 , [29] , [30] , [31] , [32] , [33] , [34] ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors confirmed that anticoagulation alone is insufficient for preventing such complications [ [25] , [26] , [27] , [28] ]. Most patients with external jugular vein aneurysm underwent surgical treatment with local, and general anesthesia [ 16 , [29] , [30] , [31] , [32] , [33] , [34] ].…”
Section: Discussionmentioning
confidence: 99%
“…Because the technique is less invasive, it can be performed under local anesthesia [ 35 , 36 ]. Moreover, in asymptomatic patient conservative management is preferable [ 2 , 33 , [37] , [38] , [39] ]. However, due to the scarcity of published research, there are no precise guidelines for the managing of these lesions.…”
Section: Discussionmentioning
confidence: 99%
“…2,9,14,16,17 The management modalities for an aesthetically disfiguring and complicated aneurysm include surgical excision or endovascular coil embolization. 17 The treatment of choice for saccular aneurysms of the EJV is complete surgical excision without venous reconstruction through a longitudinal, lateral neck incision under general or local anesthesia with minimal intraoperative and postoperative complications. Intravenous coil embolization, along with percutaneous injection of sclerosant foam, has recently emerged as a minimally invasive alternative.…”
Section: Discussionmentioning
confidence: 99%
“…Fusiform aneurysms are mostly congenital and will usually present in childhooddthey are also called phlebectasia. 3 Saccular aneurysms are mostly acquired and typically occur in adults. They can evolve spontaneously, secondarily from tumor, trauma, or inflammation, or be iatrogenic after neck surgery or catheterization.…”
mentioning
confidence: 99%
“…Although the natural history of a neck vein aneurysm is considered benign, a thrombosed external JVA (EJVA) causing undetected pulmonary embolism has been previously reported. 3 The management of JVA is controversial. To date, only three reviews of internal JVAs (IJVAs) have been reported.…”
mentioning
confidence: 99%